Necrotizing Fasciitis: A Retrospective Review of the Microbiological Aspects and Factors Associated with Multi-Drug Resistance from a Saudi Tertiary Care Hospital - Abd El-Hamid El-Kady R; Ahmed Mansour A; ElGuindy AMF (International Journal of General Medicine)
Rania Abd El-Hamid El-Kady,1,2 Ahd Ahmed Mansour,3 Ahmed Mahmoud Fouad ElGuindy4,5 1Department of Medical Microbiology and Immunology, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 2Pathological Sciences Department, MBBS Program, Fakeeh College for Medical Sciences, Jeddah, 21461, Kingdom of Saudi Arabia; 3Medical Laboratory Sciences Department, MLS Program, Fakeeh College for Medical Sciences, Jeddah, 21461, Kingdom of Saudi Arabia; 4Department of Orthopedic Surgery, Faculty of Medicine, Fayoum University, Fayoum, Egypt; 5Department of Musculoskeletal System, My Clinic International, Jeddah, Kingdom of Saudi ArabiaCorrespondence: Rania Abd El-Hamid El-Kady, Pathological Sciences Department, MBBS Program, Fakeeh College for Medical Sciences, P.O. Box 2537, Jeddah, 21461, Kingdom of Saudi Arabia, Tel +966569849897, Email raalkadi@fcms.edu.saBackground: Necrotizing fasciitis (NF) is a potentially lethal soft tissue infection, with a high rate of morbidity and mortality. Data on the microbiological aspects of NF from Saudi Arabia are extremely lacking. Thereby, we endeavored in this study to highlight the microbial causes of NF and their antimicrobial resistance profiles, as well as the risk factors and independent predictors for development of multi-drug resistant (MDR) strains.Methods: Over a period of three years, we retrospectively reviewed the medical, intraoperative, and laboratory electronic records of adult patients diagnosed with NF in our institution. We analyzed the risk factors for acquisition of MDR-NF using univariate analysis, whereas a multivariate regression model was generated to identify the independent predictors for MDR-NF.Results: Out of 38 adult patients diagnosed with NF, 27 (71.1%) were males and the mean age was 60.11 ± 13.57 years. The lower extremities were the most common site for NF (36.8%). Overall, monomicrobial NF (58%) was more frequent than the polymicrobial type (42%). A relatively high rate of MDR organisms was identified amongst the Gram-negative isolates (33.3%). Risk factors for MDR-NF included increased hospital length of stay, intensive care unit (ICU) admission, old age, coexisting malignancy, and increased Laboratory Risk Indicator for Necrotizing Fasciitis score. The multivariate analysis identified lengthy hospital stays and ICU admission as the independent predictors for MDR infections.Conclusion: Our study showed that MDR-NF is a growing challenge in clinical practice that poses negative impacts on the patient outcomes as well as health care resources. On that premise, it is crucial to enforce antimicrobial stewardship guidelines, and to improve our infection control policies to mitigate the escalating surge of MDR organisms. Furthermore, thorough active surveillance studies and enhanced collaboration amongst healthcare professionals are pivotal for early recognition and intervention.Keywords: antibiotics, mortality, multi-drug-resistant, necrotizing fasciitis, pathogen, risk factors